(untitled) (Minerva, 2019)
Salus rei publicae is a standard expression of the Latin political vocabulary that implies the personification of the state. In this paper we study how this personification works as a tool of pathos used to build the opponent’s identity as hostis publicus and his own identity as a savior within the ciceronian oratory between 63 BC and 52 BC.